A review of the recycling of rare earth metals. (October 2015) - Ferron, C. J.; Henry, P.
Abstract : Although rare earth metals are more abundant than their name would indicate, disruptions of their supplychain have occurred recently, and it is no surprise thatthe US Department of Energy (DOE) and the European Union (EU) Commission have listed several of them as critical for their role as materials essential for a clean society. This paper briefly reviews the major uses for rare earth metals and identifies the potential sources of scrap for recycling. The paper then describes the various processes developed to recycle rare earth-containing scraps, such as spent Ni-metal hydride (MH) batteries, magnets, catalysts, polishing powders and phosphors, with case studies taken from industrial practice and research work. The success of recycling efforts depends not only on adequate technical advancements but also requires the overcoming of non-technical challenges comprising, among others, logistics (collection, transportation), and an appropriate political and legal framework.